Tinjauan Hukum terhadap Efektivitas Sistem Pencatatan dan Pelaporan Barang Logistik pada Satuan Brimob Polda Sumatera Utara - Nuryanto; Syahrul Bakti Harahap (Jurnal Begawan Hukum (JBH), 2025)
This research is motivated by the importance of an effective logistics recording and reporting system in supporting operational performance and security within the Mobile Brigade (Brimob) Unit of the North Sumatra Regional Police. Logistics items such as firearms, ammunition, and other operational equipment are classified as State-Owned Goods (BMN), which must be managed orderly, transparently, and accountably in accordance with prevailing legal provisions, such as Law No. 1 of 2004, Government Regulation No. 27 of 2014, and Police Chief Regulation No. 10 of 2011. Problems arise when the logistics system faces technical constraints, lack of personnel training, and weak oversight, which in some cases have led to the loss of strategic items such as firearms.The aim of this study is to analyze the implementation of the logistics recording and reporting system in the Brimob Unit of the North Sumatra Regional Police in accordance with legal provisions, assess its effectiveness in supporting operational duties, and identify existing challenges and improvement efforts. This research uses an empirical juridical method with a qualitative approach, through document studies and interviews with logistics and operational personnel.The research findings indicate that the recording and reporting system has been carried out in an orderly and accountable manner, utilizing both manual and digital systems in parallel. There is a strong commitment among personnel to comply with SOPs, use dual-recording as risk mitigation, and maintain regular reporting in accordance with standards. Nonetheless, challenges remain in the form of limited technological infrastructure, the need for continuous personnel training, and integration with national logistics systems. Strategic efforts have been made through capacity building, gradual digitalization, and strengthening of SOPs and internal audits. Overall, the system is considered effective in supporting the unit's tasks and reflects the principles of administrative law, namely legality, accountability, and orderly administration.